1992
DOI: 10.1111/j.1365-2621.1992.tb14308.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Ray Processing to Destroy Staphylococcus aureus in Mechanically Deboned Chicken Meat

Abstract: Gamma radiation doses of 0.26 kGy and 0.36 kGy, administered in vacua at O'C, destroyed 90% of log-phase and stationary-phase colony forming units (CFU) of Staphylococcus aureus ATCC 13565 (FDA 196E), respectively, in mechanically deboned chicken meat (MDCM). Samples inoculated with 1Oa.g CFU/g of S. aureus were treated with gamma radiation in vacua at 0°C and then held for 20 hr at 35°C (abusive storage). Viable CFU were found in samples irradiated to 0.75 kGy but not in those irradiated to I.50 kGy either be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 12 publications
5
12
1
Order By: Relevance
“…The results of this work are similar to those reported by some authors who have observed that 2.5 kGy is an efficient dose of radiation to inhibit the growth of Salmonella and increase the shelflife of refrigerated chicken meat (Thayer & Boyd, 1992;Lescano et al, 1991;Lamuka et al, 1992). Similar results were observed by Hanis et al (1989) who concluded that, despite this dose of radiation is not enough to promote pasteurization of the product, the microorganisms are greatly affected by the interaction between radiation and refrigeration.…”
Section: Salmonella Typhimuriumsupporting
confidence: 81%
See 1 more Smart Citation
“…The results of this work are similar to those reported by some authors who have observed that 2.5 kGy is an efficient dose of radiation to inhibit the growth of Salmonella and increase the shelflife of refrigerated chicken meat (Thayer & Boyd, 1992;Lescano et al, 1991;Lamuka et al, 1992). Similar results were observed by Hanis et al (1989) who concluded that, despite this dose of radiation is not enough to promote pasteurization of the product, the microorganisms are greatly affected by the interaction between radiation and refrigeration.…”
Section: Salmonella Typhimuriumsupporting
confidence: 81%
“…Thayer & Boyd (1992) didn't find viable CFU of Staphylococcus aureus in mechanically deboned chicken meat inoculated with 8.0x10…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…Therefore, it is important to eliminate the organism before toxin is produced (Jay, 1992). Thayer and Boyd (1992) studied the effects of irradiation on Staphylococcus aureus. They reported that package environment did not significantly effect Dio values.…”
Section: Pathogenic Organismsmentioning
confidence: 99%
“…But, the stage of growth was important to radiation sensitivity, with cells in the mid-log phase being more susceptible to irradiation. Thayer and Boyd (1992) and both stated that a dose of 3.0 kGy would reduce a 5. aureus population by 6.3 log cycles. Eliminating viable S. aureus cells from the raw meat is critical and is necessary before the cells can produce enterotoxin.…”
Section: Pathogenic Organismsmentioning
confidence: 99%
“…Radiation processing of food is an upcoming and potential food safety technology for improving hygiene and increasing storage and distribution life. Ionising radiation is used to convey beneficial alterations in food stuffs and it has been recommended as a method of ensuring the safety of meat products 1 . The wholesomeness and acceptability of irradiated foods have been evaluated by various expert committees like Joint Expert Committee on Food Irradiation (JECFI), International Atomic Energy Agency (IAEA), World Health Organisation (WHO) and Food and Agriculture Organisation (FAO) and after reviewing all the data it was recommended that the irradiation of any food commodity up to an overall average dose of 10 kGy, presents no toxicological hazard as well as no nutritional or microbiological problem.…”
Section: Introductionmentioning
confidence: 99%